Impact of T i/T e ratio on ion transport based on EAST H-mode plasmas - LIU, Jianwen; ZANG, Qing; LIANG, Yunfeng; CHEN, Jiale; WU, Xiaohe; KNIEPS, Alexander; HU, Jiahui; JIN, Yifei; ZHANG, Bin; CHU, Yuqi; LIU, Haiqing; LYU, Bo; et al. (Plasma science & technology, 2024)
At the EAST tokamak, the ion temperature ( T i ) is observed to be clamped around 1.25 keV in electron cyclotron resonance (ECR)-heated plasmas, even at core electron temperatures up to 10 keV (depending on the ECR heating power and the plasma density). This clamping results from the lack of direct ion heating and high levels of turbulence-driven transport. Turbulent transport analysis shows that trapped electron mode and electron temperature gradient-driven modes are the most unstable modes in the core of ECR-heated H-mode plasmas. Nevertheless, recently it was found that the T i / T e ratio can increase further with the fraction of the neutral beam injection (NBI) power, which leads to a higher core ion temperature ( T i0 ). In NBI heating-dominant H-mode plasmas, the ion temperature gradient-driven modes become the most unstable modes. Furthermore, a strong and broad internal transport barrier (ITB) can form at the plasma core in high-power NBI-heated H-mode plasmas when the T i / T e ratio approaches ~1, which results in steep core T e and T i profiles, as well as a peaked n e profile. Power balance analysis shows a weaker T e profile stiffness after the formation of ITBs in the core plasma region, where T i clamping is broken, and the core T i can increase further above 2 keV, which is 80% higher than the value of T i clamping in ECR-heated plasmas. This finding proposes a possible solution to the problem of T i clamping on EAST and demonstrates an advanced operational regime with the formation of a strong and broad ITB for future fusion plasmas dominated by electron heating.